Rekonstruksi Sistem Kendali Internal Pesantren Dalam Mitigasi Kasus Kekerasan Seksual: Analisis Kebijakan PMA Nomor 73 Tahun 2022 - Rangga Pratama Saputra; Sabarudin Sabarudin; Awla Putri Adibah (CV. ITTC INDONESIA, 2026)
The increasing prevalence of sexual violence cases in Islamic boarding schools (pesantren) over the past decade has prompted a policy response from the Ministry of Religious Affairs through Minister of Religious Affairs Regulation (PMA) Number 73 of 2022 concerning the Prevention and Handling of Sexual Violence in Educational Institutions under the Ministry of Religious Affairs. This study aims to analyze the extent to which the provisions of PMA Number 73 of 2022 contribute to the reconstruction of the Internal Control System (ICS) of pesantren as an instrument for mitigating sexual violence. The study employs a qualitative approach using document content analysis. Primary data were obtained from the text of PMA Number 73 of 2022, while secondary data consisted of academic literature, reports from government institutions, and comparative policy documents. The findings indicate that PMA Number 73 of 2022 normatively accommodates the five core components of the Internal Control System—control environment, risk assessment, control activities, information and communication, and monitoring. However, significant implementation gaps remain, particularly regarding whistleblower protection, competency standards for handling teams, and trauma-informed victim recovery mechanisms. This study contributes to the development of an institutional governance framework for protection that is contextually relevant to religious educational institutions.